Investigation of product quality using virtual manufacturing on forging, punching-stamping and welding / Azrriq Zainul Abidin - Zainul Abidin, Azrriq (2016)
In this master dissertation, selected manufacturing process are to be investigated with the aid of FEM/FVM simulation and the quality of the products are further analysed based on actual results. This research consist of case studies which are bulk forming, sheet metal and welding process. The first case study is divided into three (3) focuses namely: product quality analysis of water meter housing made of zinc-copper-alloy, die stress analysis for piston manufacturing and process analysis of multistage hot forging process. The parameters for simulation study were obtained from manufacturing companies. In the second case study, sheet metal forming process punching and stamping is to be investigated in term of spring back behaviour. The material of sheet metal is aluminium and mild steel. The third case study focuses on the investigation of weld induced distortion which was affected by clamping release time. GMAW welding process are simulated on a T-joint double fillet weld with mild steel as parent material. The experiments were carried out using universal forming machine and fully automatic GMAW in laboratory conditions for second and third case study respectively. The simulation result are further compared with the experimental results and it shows good agreement. Besides, simulation can provide detailed information necessary for process and design. It can be also concluded that FEM/FVM simulation technique can be applied to replace the current practice of trial and error method within research & development (R&D) stage.